'Sanctifying Sex': Exploring 'Indecent' Sexual Imagery in Pentecostal Liturgical Practices - Sarojini Nadar; Johnathan Jodamus (Journal for the Study of Religion)
Pentecostalism, like many other church traditions, is well known for its fixation with doctrinal dualisms which enforce a separation of body and spirit, and a Puritan sexual ethic. These conservative sexual norms have led to the policing of bodies and sexual practices. As a result, instead of encouraging safer sexual practices, the churches have been known to enforce abstinence outside of marriage, or sexual restrictions within it, thus marking sex in general as 'indecent'. Some of the consequences of this repression of sexuality are young people being forced into early marriages to avoid 'living in sin', teenage pregnancies as a consequence of not wanting to disobey the church's teaching on sex and contraceptives, as well as more serious consequences of unbridled sexual expressions resulting in sexually transmitted viruses. The consequences of a repressed sexuality are indeed serious. However, what if this 'repressive hypothesis' can be challenged within Pentecostal spaces? What if, like Foucault suggests, a deeper engagement with the subject matter would show, not sexual censorship, but rather a re-channeling of sexuality? Drawing on Foucault's challenge to the repressive hypothesis, where he suggests that so-called repressed sexuality finds 'appropriate' outlets in spaces such as psychiatry and prostitution, this essay suggests a third outlet, namely Pentecostalism. While particular sexual discourses may be constructed as indecent and contaminated as 'sin', liturgical and deliverance practices ironically signify erotic relationships between the divine and the believer. Proceeding with an 'indecent' theological lens, as proposed by Marcella Althaus-Reid, we argue that Pentecostalism's liturgical practices ironically and unconsciously open up possibilities for more embodied, real, and sexed experiences of the divine. This consideration not only expands the interpretive possibilities for how we mark relationships with the divine, but also how sexual relationships between humans are shaped and possibly destigmatized. In taking a sneak peek 'under God's skirt', in Althaus-Reid's words, we reimagine the indecent as sacred. Through an analysis of how bodies and rituals are marked by discursive practices within the songs and performances in these churches and an examination of a blasphemy case, this essay lays bare the critical spaces available for more embodied theologies - 'sexual healing' that perhaps even the worshipers themselves have unconsciously ignored.